(untitled) (Indian Journal of Animal Production and Management, 2015)
A small herd of Punganur animals (154) are being maintained at Livestock Research Station, Palamaner under Sri Venkateswara Veterinary University as a part of in situ conservation. The data was collected on birth weight, biometrical measurements and certain physical traits. The average birth weights of male and female calves were 10.80 ± 0.48 kg and 10.80 ± 0.79 kg, respectively. The mean height at withers, body length, chest girth , paunch girth, pin bones width, poll length, tail length, and ear length in male calves in the present study were 46.4±1.04, 43.80 ± 1.12, 47.30 ± 1.26, 45.70 ± 1.40, 7.70 ± 0.68, 18.40 ± 0.93, 27.80 ± 1.58, 8.60 ± 0.68 cm, respectively while in female calves the corresponding values were 50.0 ± 2.40, 43.5± 1.26, 47.9 ± 1.44, 47.9 ± 1.22, 8.0 ± 0.72, 19.8 ± 1.00, 30.3 Biometrical measurements of Punganur cattle ± 1.95, 9.2 ± 0.52 cm ,respectively. The average total lactation milk yield was 279.8 ± 51.18 litres with a lactation length of 95.3 ± 21.47 days. The daily average milk yield and peak yields were 2.4 ± 0.33 and 2.6 ± 0.34 liters, respectively with an average 5.4 % fat and 9.53 % S.N.F. The average age at first calving, service period and gestation period were 1540.2 ± 242.86 days, 129.1±17.36 days and 276.9±0.79 days, respectively.